2022
DOI: 10.1093/sleep/zsac022
|View full text |Cite
|
Sign up to set email alerts
|

Order matters: sleep spindles contribute to memory consolidation only when followed by rapid-eye-movement sleep

Abstract: Sleep is known to benefit memory consolidation, but little is known about the contribution of sleep stages within the sleep cycle. The sequential hypothesis proposes that memories are first replayed during non-rapid-eye-movement (NREM or N) sleep and then integrated into existing networks during rapid-eye-movement (REM or R) sleep, two successive critical steps for memory consolidation. However, it lacks experimental evidence as N always precedes R sleep in physiological conditions. We tested this sequential h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…We found that the hippocampus helps to build neocortical representations of the new environment during NREM sleep (as in Simulation 1) and the neocortex then reinstates the old environment during REM sleep, allowing careful integration of the new information into neocortex without overwriting the old. Our proposal is strongly consistent with studies suggesting that memory reactivation during SWS sets up subsequent integration into existing knowledge during REM (59, 60), and more generally with the idea that both NREM and REM sleep are critical for memory integration, with the ordering of the stages being consequential (61, 62).…”
Section: Discussionsupporting
confidence: 90%
“…We found that the hippocampus helps to build neocortical representations of the new environment during NREM sleep (as in Simulation 1) and the neocortex then reinstates the old environment during REM sleep, allowing careful integration of the new information into neocortex without overwriting the old. Our proposal is strongly consistent with studies suggesting that memory reactivation during SWS sets up subsequent integration into existing knowledge during REM (59, 60), and more generally with the idea that both NREM and REM sleep are critical for memory integration, with the ordering of the stages being consequential (61, 62).…”
Section: Discussionsupporting
confidence: 90%
“…Our proposal is strongly consistent with studies suggesting REM is important for integrating new information with existing knowledge ( 66 ) and that this process is set up by prior memory reactivation during slow wave sleep ( 67 , 68 ). It is also consonant, more generally, with the idea that both NREM and REM sleep are critical for memory integration, with the ordering of the stages being consequential ( 69 , 70 ).…”
Section: Discussionmentioning
confidence: 93%
“…[53] NT1 patients often have naps starting in REM-sleep and then continuing to non-REMsleep (NREM), and the study found that sleep spindles only were associated with memory consolidation when the naps started with NREM-sleep followed by REM-sleep. [53] However, studies have indicated that possible memory deficits in NT1 patients seem to be limited to specific memory functions and there have been some indications of alterations of procedural memory with less effective memory consolidation as well as impaired working memory. [54] Previous structural MRI studies of narcolepsy patients [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] have revealed conflicting results involving various brain regions.…”
Section: Discussionmentioning
confidence: 99%